Diseño de un sistema de elevación de una tea portátil para el quemado de gases de pozos petroleros de prueba (2016)
During the process of this project we proceeded to evaluate alternatives for the system of elevation of the duct of a flare stack or also known like torch of gas burning, having as its starting point the conceptual design of the structural system of a trailer of load that was provided By the company SERVIMECOL where it was determined as a better option a hydraulic system for the lifting of the duct of the flare stack and the positioning and centering of the same in the platform of the trailer of load. The design was made in detail by determining and dimensioning the critical points of the system to achieve optimum performance and after that, an analysis was performed using the software of Autodesk inventor performing a modeling and simulation of the most critical elements of the systems, whose Elements were previously calculated manually and the results were corroborated to meet the requirements of a conventional flare stack.